Analysis of Gen Z Preferences Towards Digital Payment Qris for Motorcycle Parking Fees - Lailatun Mubarokah (Dinasti International Journal of Economics, Finance & Accounting, 2025)
In recent years, digital payments have transformed the way people manage financial transactions, including for small-scale payments such as motorcycle parking fees. This study investigates the preferences of Generation Z towards using QRIS (Quick Response Code Indonesian Standard) for motorcycle parking fees. This article discusses a study that analyzes the adoption of QRIS (Quick Response Code Indonesian Standard) payments among Generation Z in the motorcycle parking fee sector on the island of Java. The research method used is a survey with a questionnaire, and data processing employs the Rasch Model, a theory of item response that describes the relationship between respondents' abilities and the difficulty level of the items. The research results indicate that performance expectations and social support significantly influence Generation Z's decision to adopt QRIS, while the main challenges faced are related to personal data security and internet network infrastructure. QRIS is considered a practical and efficient payment solution that helps address cash issues in situations like parking payments. The research is limited to Gen Z preferences, QRIS payment methods, and specific areas, so the results may not be representative of the broader population. Respondent bias and limited access to technology and data also affect outcomes. This research examines how QRIS can bolster the digital economy during challenging times by promoting financial inclusion and supporting small to medium-sized businesses. It offers valuable insights for stakeholders to enhance QRIS adoption and address these challenges.